2006
DOI: 10.1044/1092-4388(2006/078)
|View full text |Cite
|
Sign up to set email alerts
|

Song Recognition by Children and Adolescents With Cochlear Implants

Abstract: Current implant processors provide insufficient spectral detail for some aspects of music perception, but they do not preclude young implant users' enjoyment of music.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
97
2
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(107 citation statements)
references
References 41 publications
5
97
2
3
Order By: Relevance
“…For one thing, they confirm child implant users' long-term memory for music, as indicated by their recall of several features of the songs, most notably their temporal form. Previous research has indicated that deaf children with implants can identify familiar recordings of popular songs from the original, vocal-plus-instrumental renditions or from the original instrumental portions (Vongpaisal et al, 2006). They can also identify the sound tracks of familiar television programs (Mitani et al, in press;Nakata et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For one thing, they confirm child implant users' long-term memory for music, as indicated by their recall of several features of the songs, most notably their temporal form. Previous research has indicated that deaf children with implants can identify familiar recordings of popular songs from the original, vocal-plus-instrumental renditions or from the original instrumental portions (Vongpaisal et al, 2006). They can also identify the sound tracks of familiar television programs (Mitani et al, in press;Nakata et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Like adults, congenitally deaf children are unable to identify frequently heard melodies on the basis of pitch cues alone (Stordahl, 2002;Vongpaisal, Trehub, & Schellenberg, 2006), but they can identify familiar pop songs from the original recordings or from the original instrumental portions (Vongpaisal et al, 2006). Such children can also identify the musical soundtracks from their favorite television programs (Mitani et al, in press;Nakata et al, 2005).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Research into the pitch perception abilities of child CI users has predominantly involved song recognition tasks and has consistently shown that CI users score significantly lower than their NH counterparts, particularly for songs devoid of lyrics [11,12,13]. This implies that recipients are more dependent upon rhythm and speech information, and are less able to utilise pitch information.…”
Section: Pitch Perceptionmentioning
confidence: 99%